Teaching tools: digital image manipulation in radiology (by manipulating the kV Value with constant mA) / Nur Haizum Suhaili - Suhaili, Nur Haizum (2007)
There are no teaching tools to help the lecturers who teach radiology in Fakuiti Sains Kesihatan to differentiate between the good and not accepted x-ray images. By integrating multimedia element in learning process, it will help to motivate the student and encourage them to participate in the learning process and improving their understanding in the subject. The system development and design is based on multimedia methodology and multimedia design principles. The findings clarify the basic criteria for multimedia interface design.